Cardiovascular Pediatric Critical Illness and Injury - Wheeler, Derek S. (Springer, 2017)
The field of critical care medicine is in the midst of a dramatic change. Technological and scientific advances during the last decade have resulted in a fundamental change in the way we view disease processes, such as sepsis, shock, acute lung injury, and traumatic brain injury. Pediatric intensivists have been both witness to and active participants in bringing about these changes and it is imperative that all physicians caring for critically ill children in this new era have a thorough understanding of the applicability of these modern developments to the care of patients at the bedside and to keep up with the rapidly evolving field of critical care medicine.